Quantitative pulmonary pharmacokinetics of tetrandrine for SARS-CoV-2 repurposing: a physiologically based pharmacokinetic modeling approach - Wang, Furun; Dong, Liuhan; Hu, Juanwen; Yang, Shijie; Wang, Lingchao; Zhang, Zhiwei; Zhang, Wenpeng; Zhuang, Xiaomei (Frontiers in Pharmacology, 2024)
Tetrandrine (TET), a medication traditionally utilized for silicosis in China, demonstrated anti-SARS-CoV-2 potential in vitro. Recognizing the disparity between in vitro findings and in vivo performance, this study aimed to estimate the free lung concentration of TET using a physiologically-based pharmacokinetic (PBPK) model, thereby linking in vitro activity and in vivo efficacy. Comparative pharmacokinetic studies of TET were performed in rats and dogs to elucidate the pharmacokinetic mechanisms, as well as to discern interspecies variations. These insights facilitated the creation of an animal-specific PBPK model, which was subsequently translated into a human model following thorough validation. Following validation of the pharmacokinetic profile from a literature report on single oral dosing of TET in humans, plasma and lung concentrations were predicted after TET administration at approved dosage levels. Finally, the antiviral efficacy of TET in humans was assessed based on the free drug concentration in the lungs. Both in vivo and in vitro experiments confirmed that the systemic clearance of TET is primarily contributed by hepatic metabolism. Additionally, the lysosomal capture of basic TET was identified as a pivotal factor in its vast distribution volume and heterogeneous tissue distribution, which may modulate the absorption dynamics of TET in the gastrointestinal tract. Notably, the PBPK model-calculated unbound lung concentrations of TET (1.67~1.74 μg/mL) at the recommended clinical dosage surpassed the in vitro threshold for anti-SARS-CoV-2 activity (EC90=1.52 μg/mL). In conclusion, a PBPK model was successfully developed to bridge in vitro activity and in vivo target exposure, which could facilitate TET's repurposing.